Overpressure formation mechanism in deep and ultra-deep layers in middle section of southern margin of Junggar Basin and its relationship with reservoir formation: a case study of Hutan 1 gas reservoir - Zhixin TIAN; Gang LIU; Xukai PENG; Changyu FAN; Gang WANG (Shiyou shiyan dizhi)
In recent years, breakthroughs have been continuously made in deep and ultra-deep oil and gas exploration in the southern margin of the Junggar Basin. Overpressure is commonly developed in the deep and ultra-deep layers of this area. Clarifying the overpressure formation mechanism and its relationship with oil and gas enrichment is of great significance for guiding oil and gas exploration in these areas. In this study, the pressure distribution characteristics in the deep and ultra-deep layers of the southern margin were analyzed using drill stem test (DST)-measured pressure data. The complex overpressure formation mechanism in Hutan 1 (HT1) gas reservoir was identified through comprehensive analysis of mudstone compaction curves, VES-VP cross-plots, and DEN-VP cross-plots. Based on the acoustic emission experiments and stress field simulations, the relationship between overpressure and oil and gas accumulation in HT1 gas reservoir was analyzed and discussed. The analysis showed that: (1) Except for the first row of thrust belts at the mountain front, extremely strong overpressure with a pressure coefficient greater than 2.0 was widely developed in the deep and ultra-deep layers of the southern margin. Vertically, overpressure was distributed in the thick mudstone of the Tugulu Group and its underlying strata. Horizontally, strong overpressure mainly developed in the second and third rows of structural belts at the mountain front in the middle section of the southern margin and in the Sikeshu Sag in the western section. (2) Comprehensive analysis identified that the overpressure in HT1 gas reservoir was caused by undercompaction and structural compression. Regional rapid deposition of thick mudstone caused undercompaction-associated overpressure, while the strong north-south trending compressive stress exerted by the Tianshan uplift during the late Himalayan Movement onto the southern margin caused structural compression overpressure in the deep and ultra-deep layers. (3) The formation of fluid overpressure in the deep layers promoted the folding deformation of the anticline trap in the Qingshuihe Formation of HT1 gas reservoir, forming an optimal area for oil and gas accumulation. Meanwhile, it changed the fluid dynamic field pattern around the Huxi anticline, increasing the gas potential gradient and enhancing the natural gas migration dynamics, thus providing favorable dynamic conditions for oil and gas enrichment in the Huxi anticline.